2020
DOI: 10.4038/jas.v15i1.8668
|View full text |Cite
|
Sign up to set email alerts
|

Compliance of small-scale Organic Tea Farmers with Organic Standards: A Study in Sri Lanka

Abstract: Purpose: Authenticity of organic tea has been questioned recently due to some evidence of contaminated organic tea in the market. Although producers' compliance with organic standards (OS) is a necessity to ensure the safety of organic tea and consumers' trust, the lack of empirical studies has become a timely need to understand the authenticity of organic tea production systems. Therefore, this study attempts to investigate the certifi ed organic tea (COT) farmers' compliance behaviour with OS using a study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The investigation, however, seeks confirmation in the form of personal testimonies of real bio farmers. This evidence aims to deny or reinforce existing assumptions about possible violations and adds to the body of evidence of older and more recent findings of other investigations: Zorn et al (2013), Bar and Zheng (2019), European Court of Auditors ( 2019), Karalliyadda and Kazunari (2020), Zezza et al (2020), Miśniakiewicz et al (2021), andNowicki et al (2021). Finding effective ways to prevent and significantly reduce the likelihood of possible violations by some organic farmers is the motivation for the second objective of this study.…”
Section: Anonymous Survey Of Bio Farmersmentioning
confidence: 80%
“…The investigation, however, seeks confirmation in the form of personal testimonies of real bio farmers. This evidence aims to deny or reinforce existing assumptions about possible violations and adds to the body of evidence of older and more recent findings of other investigations: Zorn et al (2013), Bar and Zheng (2019), European Court of Auditors ( 2019), Karalliyadda and Kazunari (2020), Zezza et al (2020), Miśniakiewicz et al (2021), andNowicki et al (2021). Finding effective ways to prevent and significantly reduce the likelihood of possible violations by some organic farmers is the motivation for the second objective of this study.…”
Section: Anonymous Survey Of Bio Farmersmentioning
confidence: 80%
“…The study was conducted as a cross-sectional, quantitative study utilizing a survey questionnaire prepared in a structured and closed format. It was observed that the majority of the studies on quality management practices have utilized a quantitative approach (Kim-soon et al, 2020) and it can generate a large amount of data in compliance-related studies (Karalliyadda and Kazunari, 2020). A mixed-mode survey was employed because it is the best method to generate a higher response rate than a single medium survey (Orel, 2019).…”
Section: Mixed-mode Surveymentioning
confidence: 99%
“…But the study has used the standards and recommendations as a scale of reference to determine the efforts undertaken for a quality output by the processors. As the study is having an appearance of a compliance-related study, it possesses a sensitive nature and a possibility of non-compliers operating at the commercial level to withhold participation in the survey or provide misleading answers (Karalliyadda and Kazunari, 2020).…”
Section: Nd Nd -No Significant Differencementioning
confidence: 99%